A highly conserved epitope-vaccine candidate against varicella-zoster virus induces neutralizing antibodies in mice. Issue 13 (18th March 2016) - Zhu, Rui; Liu, Jian; Chen, Chunye; Ye, Xiangzhong; Xu, Longfa; Wang, Wei; Zhao, Qinjian; Zhu, Hua; Cheng, Tong; Xia, Ningshao
Abstract: Varicella-zoster virus (VZV) is a highly infectious agent of varicella and herpes zoster (HZ). Vaccination is by far the most effective way to prevent these diseases. More safe, stable and efficient vaccines, such as epitope-based vaccines, now have been increasingly investigated by many researchers. However, only a few VZV neutralizing epitopes have been identified to date. We have previously identified a linear epitope between amino acid residues 121 and 135 of gE. In this study, we validated that this epitope is highly conserved amongst different VZV strains that covered five existing phylogenetic clades with an identity of 100%. We evaluated the immunogenicity of the recombinant hepatitis B virus core (HBc) virus-like particles (VLPs) which included amino acids (121–135). VZV-gE-specific antibodies were detected in immunized mouse serum using ELISA. The anti-peptide antiserum positively detected VZV via Western blot and immunofluorescent staining assays. More importantly, these peptides could neutralize VZV, indicating that these peptides represented neutralizing epitopes. These findings have important implications for the development of epitope-based protective VZV vaccines.